Bouwfonds Kunstcollectie - Hefting, Paul (Hoevelaken : Bouwfonds Nederlandse Gemeenten, 1985)
Armando ; Lucassen ; Benner, Gerrit ; Lataster, Ger ; Defesche, Pieter ; Diederen, Jef ; Oestreicher, Helly ; Raveel, Roger ; Haanstra, Johan ; van Bohemen, Kees ; Kortlang, Cees ; Rogge, Cornelius ; Blok, Ernst ; Rijkhart de Voogd, Thierry ; Franse, Kees ; van der Pol, Jan ; etc.
Nederlands
boek